PENGARUH KESADARAN WAJIB PAJAK, KEGIATAN SOSIALISASI PERPAJAKAN DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PPH 25 BADAN DI KPP PRATAMA MALANG SELATAAN - Rina Lailatul Qodriyah; Jeni Susyanti; M Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT This study aims to determine the effect of taxpayer awareness, taxation socialization activities and tax audit of 25 corporate income tax revenues. The sample in this study amounted to 100 corporate taxpayers and used the simple random sampling technique. The analysis was performed using multiple linear regression models. The results of this study indicate that partially taxpayer awareness has a significant positive effect on income tax 25, taxation socialization activities have a significant and no significant positive effect on PPh 25 revenue and tax audit has a significant positive effect on income tax revenue 25. While compulsory awareness tax, taxation and tax audit dissemination activities have a significant effect on the 25 corporate income tax receipts at the KPP Pratama Malang Selatan. Keywords: taxpayer awareness, taxation socialization activities, tax audits and 25 corporate income tax receipts